TransCatheter aortic valve implantation and fractional flow reserve-guided percutaneous coronary intervention versus conventional surgical aortic valve replacement and coronary bypass grafting for treatment of patients with aortic valve stenosis and complex or multivessel coronary disease (TCW): an international, multicentre, prospective, open-label, non-inferiority, randomised controlled trial - Kedhi, Elvin; Hermanides, Renicus S; Dambrink, Jan-Henk E; Singh, Sandeep K; Ten Berg, Jurriën M; van Ginkel, DirkJan; Hudec, Martin; Amoroso, Giovanni; Amat-Santos, Ignacio J; Andreas, Martin; Campante Teles, Rui; Bonnet, Guillaume; et al. (Lancet (London, England), 2025)
BACKGROUND: Patients with severe aortic stenosis present frequently (∼50%) with concomitant obstructive coronary artery disease. Current guidelines recommend combined surgical aortic valve replacement (SAVR) and coronary artery bypass grafting (CABG) as the preferred treatment. Transcatheter aortic valve implantation (TAVI) and fractional flow reserve (FFR)-guided percutaneous coronary intervention (PCI) represent a valid treatment alternative. We aimed to test the non-inferiority of FFR-guided PCI plus TAVI versus SAVR plus CABG in patients with severe aortic stenosis and complex coronary artery disease. METHODS: This international, multicentre, prospective, open-label, non-inferiority, randomised controlled trial was conducted at 18 tertiary medical centres across Europe. Patients (aged ≥70 years) with severe aortic stenosis and complex coronary artery disease, deemed feasible for percutaneous or surgical treatment according to the on-site Heart Team, were randomly assigned (1:1) to FFR-guided PCI plus TAVI or SAVR plus CABG according to a computer-generated sequence with random permuted blocks sizes stratified by site. The primary endpoint was a composite of all-cause mortality, myocardial infarction, disabling stroke, clinically driven target-vessel revascularisation, valve reintervention, and life-threatening or disabling bleeding at 1 year post-treatment. The trial was powered for non-inferiority (with a margin of 15%) and if met, for superiority. The primary and safety analyses were done per an intention-to-treat principle. This trial is registered with ClinicalTrials.gov (NCT03424941) and is closed. FINDINGS: Between May 31, 2018, and June 30, 2023, 172 patients were enrolled, of whom 91 were assigned to the FFR-guided PCI plus TAVI group and 81 to the SAVR plus CABG group. The mean age of patients was 76·5 years (SD 3·9). 118 (69%) of 172 patients were male and 54 (31%) patients were female. FFR-guided PCI plus TAVI resulted in favourable outcomes for the primary endpoint (four [4%] of 91 patients) versus SAVR plus CABG (17 [23%] of 77 patients; risk difference -18·5 [90% CI -27·8 to -9·7]), which was below the 15% prespecified non-inferiority margin (pnon-inferiority<0·001). FFR-guided PCI plus TAVI was superior to SAVR plus CABG (hazard ratio 0·17 [95% CI 0·06-0·51]; psuperiority<0·001), which was driven mainly by all-cause mortality (none [0%] of 91 patients vs seven (10%) of 77 patients; p=0·0025) and life-threatening bleeding (two [2%] vs nine [12%]; p=0·010). INTERPRETATION: The TCW trial is the first trial to compare percutaneous treatment versus surgical treatment in patients with severe aortic stenosis and complex coronary artery disease, showing favourable primary endpoint and mortality outcomes with percutaneous treatment. FUNDING: Isala Heart Centre and Medtronic.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; frakční průtoková rezerva myokardu; aortální stenóza; Humans; Coronary Artery Bypass; koronární angioplastika; Female; Aged; chirurgická náhrada chlopně; výsledek terapie; senioři; lidé; Aortic Valve Stenosis; Transcatheter Aortic Valve Replacement; transkatetrální implantace aortální chlopně; ženské pohlaví; Male; koronární bypass; Treatment Outcome; Aged, 80 and over; Percutaneous Coronary Intervention; senioři nad 80 let; Fractional Flow Reserve, Myocardial; mužské pohlaví; prospektivní studie; Heart Valve Prosthesis Implantation; Prospective Studies